Activating Transcription Factor 6 Mediates Inflammation in Experimental Varicocele-Induced Epididymal Epithelial Cells - Jin YS; Cui YQ; Xu YP; Chen J; Zhang XB; Wang X (Dove Medical Press, 2024)
Yin-shan Jin,* Yuan-qing Cui,* Yan-ping Xu,* Jie Chen, Xue-bao Zhang, Xiong Wang Department of Reproductive Medicine, Yantai Yuhuangding Hospital, Yantai, 264000, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiong Wang, Department of Reproductive Medicine, Yantai Yuhuangding Hospital, No. 20, Yuhuangding East Road, Yantai, 264000, People's Republic of China, Email wangxiong01903@163.comIntroduction: Varicocele is a dilatation of the internal spermatic vein and it is generally recognized as one cause of male infertility. This study aimed to analyze the roles of activating transcription factor 6 (ATF-6) in experimental varicocele-induced epididymal epithelial cells.Methods: Experimental left varicocele was established in rats through partial left renal vein ligation. At 8 weeks after surgery, the left epididymal damage was observed using H&E and TUNEL staining. The expressions of neutral α-glucosidase (NAG), ATF-6, tumor necrosis factor (TNF)-α, and phospho-nuclear factor (p-NF)-κB p65 (S536) in the left epididymis were measured by immunohistochemistry. ATF-6 silence in rat epididymal epithelial cells was established by ATF-6 siRNA transfection. The cells were treated with hypoxia for 24 h, and cell viability was measured by CCK-8, levels of NAG, TNF-α, and interleukin (IL)-8 in cells were measured by ELISA, levels of p-NF-κB p65 (S536)/NF-κB p65 protein in cells were measured by Western blotting.Results: The results showed that the experimental left varicocele induced hypertrophy and apoptosis of epididymal epithelial cells (p< 0.05), and decreased the expressions of NAG in the epididymal epithelial cells compared with the sham-operated control rats (p< 0.01). Meanwhile, the expressions of ATF-6, TNF-α, and p-NF-κB p65 (S536) were increased in the epididymal epithelial cells after the experimental left varicocele compared with the sham-operated control rats (p< 0.05). In the hypoxia-treated cells, ATF-6 silence increased the cell viability and decreased the levels of TNF-α, IL-8, and p-NF-κB p65 (S536) compared with the control cells (p< 0.05).Discussion: The ATF-6 pathway was activated in a rat's left varicocele-induced epididymal damage. Inhibition of the ATF-6 pathway might be a possible novel therapeutic approach for left varicocele-induced epididymal damage.Keywords: epididymal neutral α-glucosidase, hypoxia, left varicocele, nuclear factor-kappa B p65, NF-κB p65